Enhanced biological phosphorous removal by tetrasphaera - Chan, Hazel Hwee Yan (2018)
In tropical Singapore, maintaining stable EBPR with high phosphorous removal is a challenge, as GAOs are more efficient in taking up substrates at high temperatures compared to PAOs. Several studies have achieved stable tropical EBPR using different operational conditions and feeding strategies. However, Accumlibacter was the dominant PAO in these studies and an enrichment of Tetrasphaera at high temperature is lacking. This project achieved an enrichment of Tetrasphaera and reduced the abundance of Accumulibacter when glutamate was fed for two weeks and acetate for one week in Stage 4. There was orthophosphate-P removal attained throughout the experiments, regardless of the carbon source fed. At the end of Stage 4, stable EBPR was achieved with orthophosphate-P concentrations maintained at an average of 15 mg P/L. Variations in this alternating feeding strategy can be explored in future studies to achieve a highly-enriched culture of Tetrasphaera and high, stable EBPR.